MODEL OF THE INSTITUTIONAL MECHANISM OF STIMULATION OF INNOVATIVE ACTIVITY OF THE REGION: PROCESS APPROACH - Buyanova M.E.; Averina I.S.; Popova Ju.G. (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 3, Èkonomika,Èkologiâ, 2018)
The economic development of the constituent entities of the Russian Federation is the basis for strengthening the economic position of the country as a whole in the international arena. One of the key factors in improving the efficiency of the economy is innovation, the introduction of which is able not only to consolidate the position of the region (the country as a whole), but also to strengthen them compared to competitors. This circumstance determines the importance of research in the field of stimulation of innovation activity of individual subjects of the country, which allow not only to assess the existing state, but also to identify a set of problems and contradictions in the economic system of the region for their subsequent resolution and (or) leveling of negative consequences. In addition to the economic aspects that have a direct impact on the efficiency of innovative development of the region, the institutional components that form the mechanism of influence on innovative activity on the example of the Volgograd region are analyzed in the article. At the same time, the institutional mechanism itself is presented as a set of elements (actors, formal rules and informal rules, as well as incentives and constraints) involved in the process of enhancing innovation in the region. The study analyzes the indicators that reflect the effectiveness of the institutional mechanism to stimulate innovation in the Volgograd region, such as: the quality of the regulatory framework, organizational support of innovation policy, the number of small innovative enterprises, the level of educational potential, etc. These indicators reflect the effectiveness or inefficiency of the individual elements of the above-mentioned mechanism and identify the problems and contradictions that exist within its framework with a view to their subsequent elimination and the creation of additional opportunities for the development of the regional economic system in order to strengthen its economic security.